Audit Committee Financial Expertise and Oversight Effectiveness Evaluation (gjstudies, 2021)
This research introduces a novel, multi-dimensional framework for evaluating theeffectiveness of corporate audit committee oversight, moving beyond the traditionalbinary classification of financial expertise. While existing literature predominantly focuses on the presence of accounting-based expertise, this study posits that oversighteffectiveness is a complex construct influenced by a confluence of cognitive diversity,experiential depth, and dynamic interaction with management. We develop and validate a composite metric, the Oversight Effectiveness Quotient (OEQ), which integratesquantitative measures of committee composition with qualitative assessments of processrigor and challenge intensity. Our methodology employs a longitudinal, multi-methodapproach, combining archival financial data analysis with a proprietary survey instrument administered to audit committee chairs, CFOs, and external auditors across asample of 150 publicly traded firms. The findings reveal a non-linear relationship between traditional measures of financial expertise and oversight outcomes, indicatingdiminishing returns beyond a threshold. More significantly, we identify ’integrativeexpertise’—the ability to synthesize financial, strategic, and risk perspectives—as astronger predictor of effective oversight than accounting proficiency alone. The results demonstrate that committees characterized by cognitive diversity and structured,evidence-based deliberation protocols are more effective in mitigating earnings management and enhancing financial reporting quality, even when controlling for standardmeasures of expertise. This research contributes a more nuanced and actionable modelfor boards, regulators, and investors to assess and enhance the true oversight capacityof audit committees, challenging the adequacy of current regulatory definitions andhighlighting the critical role of process and interaction dynamics